Study on downside risk of demand and cost behavior of local public enterprises / Shohei Nagasawa and Shoichiro Hosomi. - Nagasawa, Shohei; Hosomi, Shoichiro (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
Our study verifies cost behavior of public sector organizations by empirical techniques. First is to clarify that cost behavior of the public sector is not clear enough up to now. Second is to verify the relation between market share level and cost behavior. Last is to clarify how business managers have carried out cost management against the downside risk of demand. We used 39,803 financial data of local public enterprises of 4,342 businesses for 15 years from 1999 to 2013 for analysis. Some local public enterprises have a market share exceeding 90%. As a result of the analysis, sticky costs were confirmed throughout the local public enterprises. However, the sticky costs were confirmed regardless of the degree of monopoly. Therefore, the market share was confirmed to have no influence on cost behavior of local public enterprises. And it became clear that sticky costs strengthened cost behavior of the local public enterprises since 2006. From this fact, in the situation in which the downside risk of demand rose, it was confirmed that the local public enterprise managers could not adjust capacity due to their high fixed cost structure.